Common allergens in patients with contact dermatitis identified using patch test in a tertiary care centre in North Kerala - Gopinath, V. P. K.; Simi, V. M.; Basheer Ahammed, K.; Ali Rishad, C. M.; Farisa, P. M. (International Journal of Research in Dermatology, 2019)
Background: Allergic contact dermatitis (ACD) is a disease characterised by an immune mediated response to a substance. The primary prevention remains avoidance of the implicated allergen. This is done with the help of patch test using the Indian Standard series (ISS). Methods: Out of the 246 cases of ACD that came to our Dermatology department, 92 patients were selected and subjected to patch testing using the ISS. Results were read after 48 and 96 hours, interpreted as per ICDRG criteria and were analysed. Results: From 92 patients 59.8% were males and 40.2% were females. Majority of the individuals with ACD who were patch tested belonged to the age range of 21-60 years accounting to 72.8%. The most affected site was the foot. 26.7% showed positivity to Black rubber mix, followed by potassium dichromate 20% and nickel 14.4%. 7.8% produced delayed reactions with positivity revealed at the final reading. One patient gave multiple positive reactions to paraben, PPD and chlorocresol. Conclusions: In the study middle aged males were mostly affected which may be influenced by the sample selected. Black rubber mix was identified as the most frequent sensitizer followed by potassium dichromate which was also implicated as the sensitizer most seen in the unskilled generally. Fragrance mix was responsible for all delayed responses yielding positivity in the second reading. When not considering the negligible left, patch tests’ results could be correlated with the clinical presentations. Patients were treated, educated on ACD and advised to refrain from exposure with suggestions of possible alternatives.